2014
DOI: 10.1111/nmo.12441
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water bolus temperature on esophageal motor function as measured by high‐resolution manometry

Abstract: This study showed changes in esophageal motility to be dependent on water temperature. Especially, MWS showed clear changes in esophageal motility at different temperatures of water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…These differences could be attributed to a functional EGJ obstruction secondary to increased intragastric pressure, forcing the esophagus to contract more vigorously and augment EGJ relaxation. Choi et al 37 compared the effect of different water temperatures on esophageal motility, and they found that in single swallows, cold water prolongs the duration of peristalsis and esophageal body contraction, warm water shortens the duration of esophageal body contraction, decreases IRP, and increases LES relaxation. In MRS, esophageal body contraction amplitude decreased with cold water.…”
Section: Resultsmentioning
confidence: 99%
“…These differences could be attributed to a functional EGJ obstruction secondary to increased intragastric pressure, forcing the esophagus to contract more vigorously and augment EGJ relaxation. Choi et al 37 compared the effect of different water temperatures on esophageal motility, and they found that in single swallows, cold water prolongs the duration of peristalsis and esophageal body contraction, warm water shortens the duration of esophageal body contraction, decreases IRP, and increases LES relaxation. In MRS, esophageal body contraction amplitude decreased with cold water.…”
Section: Resultsmentioning
confidence: 99%
“…demonstrating a failure of the decrease in the strength of both primary and secondary peristalsis induced by cold water in treated achalasia, albeit not in patients with nonobstructive dysphagia. In contrast, another study of healthy subjects reproduced the effects of cold and hot water already shown with traditional manometry, especially during multiple rapid swallowing (MRS) of a high volume of water (100 mL) . Thus, at present there is no clear role for the addition of thermal stimuli during standard clinical esophageal manometry protocols.…”
Section: Esophageal Provocative Testsmentioning
confidence: 95%
“…In contrast, another study of healthy subjects reproduced the effects of cold and hot water already shown with traditional manometry, especially during multiple rapid swallowing (MRS) of a high volume of water (100 mL). 63 Thus, at present there is no clear role for the addition of thermal stimuli during standard clinical esophageal manometry protocols. Nevertheless, we would argue that the addition of high-volume cold-water MRS in patients with nonobstructive dysphagia and/or NCCP may be of clinical utility in eliciting symptomatic dysmotility.…”
Section: Esophageal Provocative Testsmentioning
confidence: 99%
“…Mechanical stimulation determined by bolus size or viscosity and thermal stimulation can alter the strength and speed of esophageal peristalsis. [1][2][3] Chemical mucosal stimulation with acid 4 and capsaicin 5,6 can increase the vigor of esophageal peristalsis. Furthermore, lidocaine administration on the esophageal mucosa changes the esophageal reflexive responses to mechanical stimulation.…”
Section: Introductionmentioning
confidence: 99%